TRENDS IN THE CLINICAL PRACTICE OF LIAISON PSYCHIATRY AT A TERTIARY CARE HOSPITAL IN LAHORE, PAKISTAN - Aamer, Irum; Pervaiz, Zainab; Qayyum, Laiba; Tariq, Muhammad Noman (Journal of Pakistan Psychiatric Society, 2024)
Objectives: To ascertain the trends in referrals made to the Department of Psychiatry from all other departments of Mayo Hospital, Lahore, Pakistan. Study design: Descriptive cross-sectional research design. Place and duration of study: Mayo hospital, Lahore, Pakistan. Six months (Dec,2023-June,2024) Methodology: Convenience sampling was used to select participants, consisting of patients admitted to all wards at Mayo Hospital requiring Psychiatric consultation. Patients were enrolled using a pre-designed online form. Data included details of participants’ age and gender, number and type of consultation, reason for hospital admission, reason for referral, active complaints, past psychiatric history, mental status examination, co-morbidities, risk of self-harm or harm to others and management plan. Informed verbal consent was obtained from each patient. Patients who refused to give informed consent were excluded. Data analysis was performed using SPSS 27. Results: 220 patients received Liaison Psychiatric services, the most patients (36.4%) were admitted in General Medicine followed by (19.5%) in General Surgery. Majority (26.8%) were adolescents and 89.1% consulted a Psychiatric service for the first time. 53.2% women received liaison Psychiatric services. History of substance use was reported by 20%. The commonest reason for admission was multiple comorbidities (16.4%). Majority of the patients were referred to Psychiatric services with symptoms of depression (21.8%), self-injurious or suicidal behavior (14.5%), altered state of consciousness (14.1%), substance use disorders (14.1%), irritability or uncooperative behavior (11.8%), acutely disturbed behavior (10.9%). Conclusion: Consultation model is being used by physicians however, there is a need to educate the clinical teams about Liaison Psychiatry model to help solve difficult liaison cases.